Institutional Investors and the Informational Efficiency of Prices - Boehmer, Ekkehart; Kelley, Eric K. (Review of Financial Studies, 2009)
[Using a broad panel of NYSE-listed stocks between 1983 and 2004, we study the relation between institutional shareholdings and the relative informational efficiency of prices, measured as deviations from a random walk. Stocks with greater institutional ownership are priced more efficiently, and we show that variation in liquidity does not drive this result. One mechanism through which prices become more efficient is institutional trading activity, even when institutions trade passively. But efficiency is also directly related to institutional holdings, even after controlling for institutional trading, analyst coverage, short selling, variation in liquidity, and firm characteristics.]